2019
DOI: 10.3390/foods8030110
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Breadfruit Flour Pasta Product

Abstract: Breadfruit (Artocarpus altilis) is grown throughout the tropics. Processing the perishable starchy fruit into flour provides a means to expand the use of the fruit. The flour can be used to develop new value-added products for local use and potential export. The purpose of this investigation was to develop a pasta product using breadfruit flour, test the sensory qualities of the breadfruit pasta product by sensory evaluation, and evaluate the nutritional composition. ‘Ma’afala’, a popular and widely distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Breadfruit flour is a gluten-free flour that has high content of starch [4] and fiber [5], as well as a variety of vitamins and minerals, like vitamin C and potassium [6]. Based on these properties, breadfruit flour has been applied as an ingredient in a variety of processed food products, including pasta [7], instant baby food [8], bread [9,10], cake [11], cookies [12], and meat [13,14]. However, it was reported that inclusion of breadfruit flour in these products should be limited in order to maintain desirable quality characteristics (i.e., high cooking yield, acceptable textural and sensory quality).…”
Section: Introductionmentioning
confidence: 99%
“…Breadfruit flour is a gluten-free flour that has high content of starch [4] and fiber [5], as well as a variety of vitamins and minerals, like vitamin C and potassium [6]. Based on these properties, breadfruit flour has been applied as an ingredient in a variety of processed food products, including pasta [7], instant baby food [8], bread [9,10], cake [11], cookies [12], and meat [13,14]. However, it was reported that inclusion of breadfruit flour in these products should be limited in order to maintain desirable quality characteristics (i.e., high cooking yield, acceptable textural and sensory quality).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of fiber-rich pasta, trained panelists assessed that the samples had a more bitter and branny flavor, more rough texture, significantly lower firmness and higher adhesiveness than the refined flour pasta [ 11 , 37 ]. At the same time, consumer studies on pasta with fiber show different results depending on the fiber source [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also processed to starch (Loos et al, 1981), flour (Nochera & Caldwell, 1992;Arcelay & Graham, 1984;Loos et al, 1981;Graham & Bravo, 1981;Olatunji & Akerele, 1978) and value-added products like chips, fries, dips, baked goods, desserts, and beverages (Ragone & Cavaletto, 2006). The breadfruit flour has also been developed as pasta product (Nochera & Ragone, 2019), breadfruit bar (Nochera & Ragone, 2016), Noodles, Manchuria, Phulka and Halwa (Ravinder et al, 2018). Breadfruit flours have high water absorption capacity indicating more hydrophilic components which can potentially be used as a thickener in viscous foods such as soups, sauces, and puddings, and in certain bakery products (Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%